(untitled) (Altre Modernità, 2024)
In this article, I will analyze two recent audiovisual works featuring women who live in different territories of Chile affected by the ongoing water crisis: Siluetas de agua (Silhouettes of Water) by Violeta Paus and La balada de las sirenas seas (The Ballad of the Dry Mermaids) by Patricia Domínguez. In dialogue with social movements that fight to defend water and to deprivatize water resources, I offer a reading of both videos as audiovisual narratives that decenter the patriarchal-colonial gaze. This is done through two aesthetic-political strategies operating at the same time: the visibilization of female agency in protecting water and ecosystems threatened by drought, and the experimentation with cinematographic, technological, and sonic resources that encourage a multisensory approach to water conflicts. The Chilean artists Violeta Paus and Patricia Domínguez thus join the voices of artistic activists that seek to decolonize the gaze and water.